As reverberações do erotismo na literatura fantástica e o caso particular de Os olhos verdes - Santos, Leandro de Negreiros Pereira dos [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The subgenre of literature called Fantastic causes curiosity and fascination to many readers and researchers, thanks to its thematic network - which includes diverse metaempirical manifestations which can be made by analysis of the fantastic effect in various instancies, such as: storyteller, characters, narratary, reader, among others. The recurrence of themes associated to eroticism is evident, as well as the way it manifests in literature. Based on this assumption, the present paper work aims to briefly explain the manifestation of eroticism and its deployment in a few narratives, as well as, in a more detailed way, the tale The green eyes written by the Spanish author Gustavo Adolfo Bécquer. Therefore, works by Romanticism and Fantastic experts, like Jacó Guinsburg, Anatol Rosenfeld, Tzvetan Todorov, Remo Ceserani, Filipe Furtado and Louis Vax, were consulted. Furthermore, it was necessary to seek theoretical support about eroticism, appealing to Marilena Chaui, Octavio Paz, George Bataille and other authors' works. Also, the main objective of this paper work is to establish a few possible readings regarding of erotic aspects in the Fantastic - especially at the Romanticism's period - by pointing intersections between elements of the configuration of a specific esthetics

A literatura fantástica é objeto de estudos e fascínio de leitores e pesquisadores, seja por sua rede temática, que abarca as mais variadas manifestações metaempíricas, seja pela análise do efeito fantástico em diferentes instâncias (narrador, personagens, narratário, leitor real etc.). O que fica patente é a recorrência de temas associados ao erotismo e a maneira como são trabalhados na literatura. Partindo desse pressuposto, neste trabalho buscou-se compreender brevemente as manifestações de caráter erótico e seus desdobramentos em algumas narrativas e, de maneira mais detalhada, no conto Os olhos verdes, do espanhol Gustavo Adolfo Bécquer. Para tanto, foram consultadas as obras de especialistas no Romantismo e na literatura fantástica, sendo alguns deles Jacó Guinsburg, Anatol Rosenfeld, Tzvetan Todorov, Remo Ceserani, Filipe Furtado e Louis Vax. Além disso, foi preciso buscar aporte teórico a respeito da temática erotismo, recorrendo-se a trabalhos como os de Marilena Chaui, Octavio Paz, George Bataille e outros. Longe de esgotar o assunto em questão, neste trabalho o objetivo é estabelecer algumas das possíveis leituras acerca do aspecto erótico na literatura fantástica - especialmente no período romântico -, apontando as interseções entre elementos na configuração de uma estética particular
Keywords: Bécquer, Gustavo Adolfo 1836-1870 Os olhos verdes; Literatura fantástica; Literatura espanhola; Erotismo; Romantismo; Fantasy literature